Farmers perceptions on dual-purpose sorghum and its potential in Zambia - Chikuta, S; Odong, T; Kabi, F; Mwala, M; Rubaihayo, P (International Journal of Agricultural Research, Innovation and Technology, 2015)
Food feed crops play a cardinal role in mixed crop-livestock production systems yet views of farmers on their usage are limited. Farmers perceptions in predominant sorghum growing areas of Zambia were solicited on socio-economic factors affecting sorghum production, awareness and willingness to adopt dual-purpose sorghum cultivars for food and feed. Preferred traits of a model dual-purpose cultivar were identified. The aim of the study was to generate information that would support the genetic improvement of dual-purpose sorghum. Questionnaires were used to generate this information. Results showed that less than 50% of sorghum growing SSFs had limited knowledge on the use of sorghum to produce feed silage; however, there was full awareness among the LSFs. Among other traits, farmers ideal variety should combine high grain yield potential (100 %) with high biomass (100 % of LSFs and 80 % of SSFs) and high stem sugar content (100 % of LSF and 70 % of SSFs). All the SSFs and 20 % of the LSFs indicated that adequate production could be hampered by low grain yield, poor access to improved seed and unavailability of farmers- preferred cultivars. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22654 Int. J. Agril. Res. Innov. & Tech. 4 (2): 76-81, December, 2014